Cultivable Skin Mycobiota of Healthy and Diseased Blind Cave Salamander (Proteus anguinus) - Zalar, Polona; Gubenšek, Ana; Gostincar, Cene; Kostanjšek, Rok; Bizjak-Mali, Lilijana; Gunde-Cimerman, Nina (Frontiers in Microbiology, 2022)
Proteus anguinus is a neotenic cave salamander, endemic to the Dinaric Karst and a symbol of world natural heritage. It is classified as “vulnerable” by the International Union for Conservation of Nature (IUCN) and is one of the EU priority species in need of strict protection. Due to inaccessibility of their natural underground habitat, scientific studies of the olm have been conducted mainly in captivity, where the amphibians are particularly susceptible to opportunistic microbial infections. In this report, we focused on the diversity of cultivable commensal fungi isolated from the skin of asymptomatic and symptomatic animals obtained from nature (20 specimens) and captivity (22 specimens), as well as from underground water of two karstic caves by direct water filtration and by exposure of keratin-based microbial baits and subsequent isolation from them. In total 244 fungal isolates were recovered from the animals and additional 153 isolates were obtained from water samples. Together, these isolates represented 87 genera and 166 species. Symptomatic animals were colonized by a variety of fungal species, most of them represented by a single isolate, including genera known for their involvement in chromomycosis, phaeohyphomycosis and zygomycosis in amphibians: Acremonium, Aspergillus, Cladosporium, Exophiala, Fusarium, Mucor, Ochroconis, Phialophora and Penicillium. One symptomatic specimen sampled from nature was infected by the oomycete Saprolegnia parasitica, the known causative agent of saprolegniosis. This is the first comprehensive report on cultivable skin mycobiome of this unique amphibian in nature and in captivity, with an emphasis on potentially pathogenic fungi and oomycetes.